Tradiciones culturales y su aporte turístico al cantón Montalvo - Godoy Aguiar, Berenice Shirley (2021)
This research focuses on Cultural Traditions and their contribution to the cultural tourism sector that the Montalvo Canton entails, province of Los Ríos, as a natural and cultural attraction that are part of the social historical heritage of the sector. The case study will use the following methodology, such as qualitative, diagnostic, descriptive and exploratory research, obtaining truthful and timely information as a result resolve the current situation within the canton. To acquire data that leads to the understanding of Cultural Expressions that contain a sense of Traditional belonging and identity, the technique of the online survey was used, through the technique of sampling for convenience and observation, it will proceed to establish the tabulation of the final data, reaching to implement the conclusions and recommendations of the case of how important tradition is, historical, cultural